Pemberdayaan Kelompok Wanita Tani Raharjo Mukti dalam Pemanfaatan Lahan dengan Budidaya Tanaman Holtikultura di Kelurahan Blitar - A.P, Caesariano; Siti Fadhilah NurrahMawati; Muhammad Rifqi Abroor; Prasmita Dian Wijayati; Laksmi Diana (EDUPEDIA Publisher, 2022)
Vegetable cultivation is a sector that is quite a lot in the agricultural sector. Blitar sub-district, Sukorejo sub-district has a women farmer group (kwt) named KWT Raharjo Mukti, and focuses on vegetable cultivation and sales of these vegetables. This raharjo mukti women farmer group has the potential to advance in the field of cultivation, but the limited knowledge of cultivation and the continuity of cultivation as well as the limitations of its marketing are obstacles in the process of cultivation and production of its commodities, so it is necessary to give a little direction so that they can devote their knowledge to the community, through community development in the village. Blitar. The long-term goals of the program are: (1) Encouraging the growth of motivation and creativity of kwt Raharjo Mukti in the process of cultivating horticultural crops so as to increase production,(2) Assisting the potential of kwt Raharjo Mukti in developing cultivation with maximum production, and (3) Helping kwt Raharjo Mukti in solving problems in cultivation, in order to build a better Blitar village. The specific target to be achieved is the production of several types of quality vegetables and processed for the Blitar Village